Phase evolution of C-(N)-A-S-H/N-A-S-H gel blends investigated via alkali-activation of synthetic calcium aluminosilicate precursors. (November 2016) - Walkley, Brant; San Nicolas, Rackel; Sani, Marc-Antoine; Rees, Gregory J.; Hanna, John V.; van Deventer, Jannie S.J.; Provis, John L.
Abstract: Stoichiometrically-controlled alkali-activated pastes containing calcium-(sodium) aluminosilicate hydrate (C-(N)-A-S-H) and sodium aluminosilicate hydrate (N-A-S-H) gels are produced by alkali-activation of high-purity synthetic calcium aluminosilicate powders. These powders are chemically comparable to the glass in granulated blast furnace slag, but without interference from minor constituents. The physiochemical characteristics of these gels depend on precursor chemical composition. Increased Ca content of the precursor promotes formation of low-Al, high-Ca C-(N)-A-S-H with lower mean chain length as determined by quantification of solid state nuclear magnetic resonance spectra, and less formation of calcium carboaluminate 'Alumino-ferrite mono' (AFm) phases. Increased Al content promotes Al inclusion and reduced crosslinking within C-(N)-A-S-H, increased formation of calcium carboaluminate AFm phases, and formation of an additional N-A-S-H gel. Small changes in precursor composition can induce significant changes in phase evolution, nanostructure and physical properties, providing a novel route to understand microstructural development in alkali-activated binders and address key related durability issues.